Comparison between Mulligan Sustained natural apophyseal glides (snags) VS McKenzie exercises in Chronic Mechanical Low back pain - Sumbal Salik, Shaista Rani, Rehana Hayat, Sana Manzoor, Amber Usama Malik,Sania Maqbool (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Low back pain is a common musculoskeletal problem of the modern society as 70-80% people of any age and gender get affected by this in their lifetime which affect their normal activities of daily living. Aim: To compare the efficacy between Mulligan SNAGs and McKenzie exercises in improving pain level, range of motions and functional status in chronic mechanic al low back pain patients. Method: A randomized control trial study was conducted on 45 patients suffering from chronic mechanical low back pain at Physiotherapy Department of Mayo Hospital Lahore from16th December to 21th January 2021.The patients were randomly allocated in three group’s i.e; Conventional and two trial groups by computerized generated list. In Conventional group; 15 patients were treated with conventional therapy. In trial groups; one was treated with Mulligan SNAGs and Conventional therapyand the other trial group were treated with McKenzie exercises and Conventional therapy 3 sessions per week. Pain measured by Numeric Pain Rating Scale (NPRS), Lumbar spine’s ranges measured by Goniometer and functional status measured by Oswestry Disability Index (ODI) at the completion of the 4 weeks treatment session. Results: NPRS scoring and Ranges showed significant improvement in all groups but NPRS significantly improved in McKenzie exercises group and significant improvement in ROM showed in Mulligan SNAGs group in all movements but there was no significant difference found between three groups comparison in improving the functional status with p-value =0.243. Practical implication: The study provides the opportunity to the patients to consider physiotherapy as an effective treatment for the mechanical low back pain. It also provides the statistical knowledge about these physiotherapy techniques and their effectiveness in treating the low back pain. Conclusion: Both the Mulligan SNAGs and McKenzie exercises are effective in treatment of Chronic lumbar pain as pain is most reduced through McKenzie exercise (3.33±1.29, p<0.000) while ranges of spine is improved through Mulligan SNAGs mobilization in all directions. Keywords: Chronic Mechanical Low back pain, Mulligan SNAGs mobilization, McKenzie exercises